Sleep habits: academic performance and behavior in primary school children - Muñoz Quintero, Alejandro; Bianchi, Susana Beatriz (Pensando Psicología, 2017)
Introduction: A reduction in sleep time or the presence of sleep alterations has considerablerepercussions in the performance of any person during wakefulness.Objectives: This study aimed to identify the relationship between sleep habits and academic performance and behavior in primary school children.Methodology: Participants were 405 children enrolled in public and private educational institutions. Parents answered the Children’s Sleep Habits Questionnaire (CSHQ) and the Behavior Assessment System for Children (BASC), while teachers assessed student performance through the Academic Performance Rating Scale (APRS).Results: Children slept 8.75 hours on average, which is less than suggested for these ages and less than found in other studies. Children from the public school had scores indicating greater difficulties in different sleep subscales with respect to students from the private school. A significant decrease in nocturnal sleep time during the week was observed as children progressed in age. Furthermore, it was possible to establish a significant positive relationship between sleep and behavior, and a negative relationship between the latter and academic performance.Conclusions: The presence of sleep problems was associated with behavioral alterations in children, which, in turn, were associated with a lower academic performance. These data highlight the importance of sleeping well as a necessary condition to achieve optimal performance at school.
Keywords: child behavior; academic performance; sleep habits; sleep